ORGANIZING AND COMPLETING OF SANITARY SURVEILLANCE OF SAKHALIN REGION TERRITORY FROM DELIVERY AND SPREADING OF SEVERE ACUTE RESPIRATORY SYNDROME - E. V. Papirenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Organizational work concerning prevention of «atypical pneumonia» delivery and spreading at the territory of region had begun in March, 2003 by treatmentandprophylactic and sanitary-and-epidemiology services. Large volume of work on guarantee of readiness of the border passing points, hospitals, and surveillance centers in the region for conducting preventive measures in case of SARS delivery into Sakhalin Region was held during Mach-July, 2003. Great importance was attached to the cooperation of all interested services and departments on account of preventing of «atypical pneumonia» delivery into the region, and also training of medical staff in this infection and explanatory work with population.